Health-Seeking behavior and its determinants for different noncommunicable diseases in elderly - Tushar Prabhakar; Manish Kumar Goel; Anita Shankar Acharya (Wolters Kluwer Medknow Publications, 2023)
Steady improvement in quality of life has led to increased survival time of elderly, especially of those with noncommunicable diseases. A study about their health-seeking behavior (HSB) and its determinants is essential for provision of comprehensive care and facilitate policy development. A cross-sectional study was conducted among 350 elderly participants over 60 years of age in an urbanized village of Delhi. Data was collected using a semi-structured questionnaire, and detailed general and systemic examination was done. Tests of significance were applied to assess the HSB with various demographic, clinico-social, and economic variables. A total of 87.4% of the study population was suffering from at least one noncommunicable disease (NCD). Majority of the study subjects' NCDs (72.66%) were diagnosed while getting treatment for a symptom of the disease. Also, 52.94% of the participants had inappropriate HSB. HSB was significantly associated with gender, age, duration of illness, and importantly with modifiable variables like the level of literacy, distance of preferred health facility, and presence of multimorbidity. HSB was found to be inappropriate in over half of the participants. Policymaking should focus on modifiable variables like education, distance of health facility, and multimorbidity, especially for commonly ignored diseases like osteoarthritis and diabetes.